Chemotherapeutic perfusion of portal vein after tumor thrombectomy and hepatectomy benefits patients with advanced hepatocellular carcinoma: A propensity score‐matched survival analysis - Yang Gao; Peng‐Xiang Wang; Jian‐Wen Cheng; Yun‐Fan Sun; Bo Hu; Wei Guo; Kai‐Qian Zhou; Yue Yin; Yuan‐Cheng Li; Jian Wang; Jun‐Feng Huang; Shuang‐Jian Qiu; et al. (Cancer Medicine, 2019)
Abstract Background Portal vein tumor thrombus (PVTT) is a common complication in hepatocellular carcinoma (HCC), signaling dismal outcomes. This study was conducted to evaluate the survival benefit of postoperative portal vein perfusion chemotherapy (PVC) in patients with HCC and PVTT. Methods A retrospective review was conducted in 401 consecutive patients with HCC and PVTT who underwent hepatic resection between January 2009 and December 2015 and 67 patients received adjuvant postoperative PVC. A propensity score matching (PSM) was used to match patients with and without PVC at a ratio of 1:1. Results After PSM, the median time to recurrence (TTR) and overall survival (OS) were significantly longer in PVC group compared with control group (12.3 vs 5.8 months, P = .001; 19.0 vs 13.4 months, P = .037; respectively). At 1, 2, 3, and 5 years, the cumulative recurrence rates in PVC group were 48.1%, 86.5%, 92.3% ,96.2%, respectively, with OS rates of 63.8%, 37.9%, 24.4%, 18.3%, respectively; whereas cumulative recurrence rates of 76.6%, 91.5%, 94.3%, and 97.2%, respectively and OS rates of 55.4%, 23.0%, 12.4%, and 12.4%, respectively were recorded for the control group. In multivariate analysis, postoperative PVC emerged as a significant predictor for TTR (hazard ratio [HR], 0.523; P = .001) and OS (HR, 0.591; P = .010). PVC could reduce early recurrence (≤1 year) rate after surgical resection (40.3% vs 64.2%, P = .006) and clinical outcomes were further enhanced by adding sorafenib to postoperative PVC. Conclusions Compared with surgical resection alone, postoperative adjuvant PVC treatment boosts survival and reduces early tumor recurrences in patients surgically treated for HCC and PVTT.